2020
DOI: 10.1144/m52-2018-53
|View full text |Cite
|
Sign up to set email alerts
|

The Jasmine Field, Blocks 30/06 and 30/07a, UK North Sea

Abstract: The high-pressure–high-temperature Jasmine Field lies 270 km east of Aberdeen in the UK Central North Sea and forms part of Chrysaor’s J-Area. Hydrocarbons were discovered at Jasmine in 2006, in Middle–Late Triassic fluvial sandstones of the Joanne Sandstone Member of the Skagerrak Formation. Appraisal proved a greater than 2000 ft hydrocarbon column and, in 2010, the Jasmine Field development was sanctioned. Five development wells were pre-drilled between 2010 and 2013, and the field was brought on line in No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Jasmine Field is one of the more recent HPHT field developments, producing first gas in 2013, in this case from fluvial sandstones of the Joanne Sandstone Member (Mbr) of the Triassic Skagerrak Fm. In contrast to the more tank-like behaviour of the Fulmar Fm HPHT reservoirs, Lawrence et al (2020) report that the Triassic reservoir showed the expected low vertical permeability due to layering, but more rapid production decline, poorer connectivity and lower deliverability than anticipated. In attributing these aspects of reservoir performance to structural heterogeneities in particular, Lawrence et al compare the production performance of Jasmine with that of Jade and Judy fields and other potentially analogous Triassic-reservoired Central Graben fields.…”
Section: Central North Seamentioning
confidence: 66%
“…Jasmine Field is one of the more recent HPHT field developments, producing first gas in 2013, in this case from fluvial sandstones of the Joanne Sandstone Member (Mbr) of the Triassic Skagerrak Fm. In contrast to the more tank-like behaviour of the Fulmar Fm HPHT reservoirs, Lawrence et al (2020) report that the Triassic reservoir showed the expected low vertical permeability due to layering, but more rapid production decline, poorer connectivity and lower deliverability than anticipated. In attributing these aspects of reservoir performance to structural heterogeneities in particular, Lawrence et al compare the production performance of Jasmine with that of Jade and Judy fields and other potentially analogous Triassic-reservoired Central Graben fields.…”
Section: Central North Seamentioning
confidence: 66%